Contribution of Applied Culinary Courses to Tourism Education - Elif Esma Karaman; Ceyhun Akyol; Ali Murat Kesemen (Journal of Tourismology)
For university students studying in the Culinary Programme and Gastronomy and Culinary Arts Department, courses that include applied culinary training are an important element in terms of internship, professional development and possible business life. Understanding the perspectives of students on applied culinary courses is of great importance in making the educational processes in educational institutions more effective and efficient. This study seeks to reveal the perspectives of the students who pursue their education in Artvin Çoruh University on applied culinary courses. It presents a complete enumeration; 147 students who studied in the relevant programme and department in the 2022-2023 education year participated in this study. To obtain data, it draws on a 28-item data collection tool, through which the students evaluated the applied culinary education, and, thus, applies the survey method. The perceptions of the participants about the applied culinary courses are analysed by different variables. This study concludes that the students believe that the culinary courses contribute to their education and practical knowledge; that they are willing and enthusiastic to attend these applied culinary courses.